Comparison of principal component analysis and biochemical component analysis in Raman spectroscopy for the discrimination of apoptosis and necrosis in K562 leukemia cells : errata - Ong, Yi Hong (2013)
An error was made in performing PCA analysis that caused the scores and loadings of the principal components to be inaccurate. Corrected results for PCA analysis and the classification accuracies based on the scores of first three principal components are reported. Since the corrected PCs scores only cause small changes to the accuracy in cell death classification, these corrections do not change the main conclusion of this work.